THE PHENOMENON OF CODE-MIXING AMONG RADIO ANNOUNCERS: A SOCIOLINGUISTIC PERPECTIVE - Eko Sulistionoa; Suhartatik (LP2M UIN Abdul Muthalib Sangadji Ambon, 2024)
This study aimed to investigate code mixing among radio announcers at one of the private radio stations in Malang city, East Java. The design of the research was descriptive qualitative that emphazised on the phenomenon of code mixing in radio broadcast by recording the announcers while they were on the air. The data analysis covered the steps of data collection, data reduction, data presentation, and conclusion. The data were collected from radio broadcasting program targeted for young people in the city of Malang, East Java. It took two-week period, encompassing ten sessions in which the announcers engaged in code mixing, mainly between the Indonesian and English. The research finding showed that there was 40 cases of Insertions, 30 cases of Alternations, and 26 cases of Congruent Lexicalization.